Austroads. - Austroads (Sydney, NSW : Austroads)
"Austroads is the association of Australasian road transport and traffic agencies. Austroads' purpose is to improve Australian and New Zealand transport outcomes by: providing expert technical input to national road and transport policy development improving the practices and capability of road agencies promoting operational consistency by road agencies. Austroads members are collectively responsible for the management of over 900,000 kilometres of roads valued at more than
Title from title screen (viewed on 10 August 2015)
Mode of access: Available online. Address as at 10/08/15
Selected for archiving
Keywords: Roads -- Australia; Transportation -- Australia; Australian